Breastfeeding with HIV: An Evidence-Based Case for New Policy. Issue 1 (March 2019) - Gross, Marielle S.; Taylor, Holly A.; Tomori, Cecilia; Coleman, Jenell S.
To help eliminate perinatal HIV transmission, the US Department of Health and Human Services recommends against breastfeeding for women living with HIV, regardless of viral load or combined antiretroviral therapy (cART) status. However, cART radically improves HIV prognosis and virtually eliminates perinatal transmission, and breastfeeding's health benefits are well-established. In this setting, pregnancy is increasing among American women with HIV, and a harm reduction approach to those who breastfeed despite extensive counseling is suggested. We assess the evidence and ethical justification for current policy, with attention to pertinent racial and health disparities. We first review perinatal transmission and breastfeeding data relevant to US infants. We compare hypothetical risk of HIV transmission from breastmilk to increased mortality from sudden infant death syndrome, necrotizing enterocolitis and sepsis from avoiding breastfeeding, finding that benefits may outweigh risks if mothers maintain undetectable viral load on cART. We then review maternal health considerations. We conclude that avoidance of breastfeeding by women living with HIV may not maximize health outcomes and discuss our recommendation for revising national guidelines in light of autonomy, harm reduction and health inequities.